THE PROCESS OF REHABILITATION OF PERSONS RELEASED FROM PENAL INSTITUTIONS: PROBLEMS AND PROSPECTS - Shohsanam Yulchiyeva; Mirkarim Raimdjanov (Web of Journals Publishing, 2024)
In this article, you can learn about the psychological condition of people who have been released from prison after a long term of imprisonment, as well as the prospects of their reintegration into society.
Keywords: Adaptation, rehabilitation, emotional exhaustion, colony, convict, crime, social adaptation, legality, humanitarianism, execution of punishment.